Pengaruh Kesadaran Lingkungan Dan Iklan Hijau Terhadap Keputusan Pembelian Produk Hijau - Erwansyah, Dedy; Rumianti, Susti; Mervita, Eda; Iskandar, Dadang Ishak (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
The increasingly worrying condition of the earth requires humans to be aware of environmental damage, and one of the efforts is to buy green products. This study will examine the effect of environmental awareness and green advertising on purchasing decisions for labelled bottled mineral water. The study population amounted to 679 who were Economics Education students from public universities in Central Java—obtained a sample based on the Slovin formula 252 students. The study used the theory of consumer purchasing decisions. Validity and reliability tests were used to test SPSS 25-assisted research instruments, followed by four prerequisite analysis tests. Multiple linear regression was used to analyze the effect of more than two independent variables. The result found that environmental awareness (0.000) and green advertising (0.000) positively and significantly impacted purchasing decisions for labelled bottled mineral water, with the magnitude of the effect being 48%. The results showed the importance of environmental awareness and green advertising to encourage students to make decisions to buy green products. Keywords : Environmentaal Awareness, Green Advertising, Purchase Decision, Green Product